2018
DOI: 10.5194/hess-2018-132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compound flood potential in Europe

Abstract: Abstract. The interaction between storm surges and inland runoff has been gaining increasing attention recently, as they have the potential to result in compound floods. In Europe, several flood events of this type have been recorded in the past century in Belgium, France, Ireland, Italy and United Kingdom. Here, we investigate the probability of joint occurrence of storm surges, precipitation, river discharges and waves. A coincidence of those factors have a potential to cause compound floods. We use several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 5 publications
6
65
0
Order By: Relevance
“…When two or more of these mechanisms occur simultaneously, flood severity may be exacerbated leading to increased coastal flood risk. Examples of compound flood events include the combination of river discharge and surges (Moftakhari et al, ; Ward et al, ), rainfall and surges (Wahl et al, , in the U.S. coasts and Wu et al, , in Australia), and rainfall, surge, and waves (Bilskie & Hagen, ; Paprotny et al, ). If these concurrent events display statistical dependencies (e.g., through a common forcing mechanism), the probability of their joint occurrence (i.e., the chance of two or more extreme conditions occurring at the same time) is higher than that expected considering separately the extremes of each variable, with a consequent increase of the likelihood of coastal flooding.…”
Section: Introductionmentioning
confidence: 99%
“…When two or more of these mechanisms occur simultaneously, flood severity may be exacerbated leading to increased coastal flood risk. Examples of compound flood events include the combination of river discharge and surges (Moftakhari et al, ; Ward et al, ), rainfall and surges (Wahl et al, , in the U.S. coasts and Wu et al, , in Australia), and rainfall, surge, and waves (Bilskie & Hagen, ; Paprotny et al, ). If these concurrent events display statistical dependencies (e.g., through a common forcing mechanism), the probability of their joint occurrence (i.e., the chance of two or more extreme conditions occurring at the same time) is higher than that expected considering separately the extremes of each variable, with a consequent increase of the likelihood of coastal flooding.…”
Section: Introductionmentioning
confidence: 99%
“…There is a considerable body of recent literature on compound flooding, that is, the simultaneous or d‐ day lagged occurrence of extreme sea levels and peak river discharges (or extreme precipitation as a proxy for flooding), in Europe (Bevacqua et al, ; Bevacqua et al, ; Paprotny et al, ; Petroliagkis et al, ) and globally (Moftakhari et al, ; Wahl et al, ; Ward et al, ; Zheng et al, ; Zscheischler et al, ). Compound flooding may lead to significant impacts and much more disastrous consequences than each of these extremes individually (Leonard et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A state-of-the-art mesoscale hydrodynamic model: CaMa-Flood is used to simulate 25 km resolution historical and projected future flows from coarse resolution GCM runoff estimates. The changes projected by different GCMs are aggregated, and associated uncertainty is quantified using two approaches: (1) where only projections made by 'robust' GCMs (i.e., those who concur on the sign of change as projected by more than 50% of the GCMs) are considered, and (2) where projections made by all GCMs are considered. In general, it was found that the spatial distribution of the projected changes is similar in the results obtained from both approaches, whereas the magnitudes (both positive and negative) are found to be larger in the first approach than in the second approach.…”
Section: Discussionmentioning
confidence: 99%
“…Floods are the most frequently occurring natural hazard in Canada and around the globe [1][2][3][4]. A number of studies have been performed in different parts of the globe to establish methods for effective quantification of floods and their associated risks [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%